1964
DOI: 10.1161/01.cir.29.5.666
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Determining Left Ventricular Mass in Man

Abstract: ARIOUS methods have been devised by others for estimating the weight of the normal heart in man by relating heart wveight to body size and age.'1-3 In other studies the weight of the left ventricle has been compared to total heart weight in postmortem hearts.' Smith's method for estimating the normal left ventricular mass has been utilized by Bing for determining left ventricular efficiency.4 Friedman, in radiographic studies of heart volume, demonstrated a relationship between the total heart volume, myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(70 citation statements)
references
References 10 publications
0
70
0
Order By: Relevance
“…10 Circumferential stresses were calculated by the method of Mirsky. 11 The method in our laboratory of analyzing the micromanometer LV pressures also provides for a calculation of the first derivative of LV pressure (dP/dt) at a variable sampling frequency.…”
Section: Discussionmentioning
confidence: 99%
“…10 Circumferential stresses were calculated by the method of Mirsky. 11 The method in our laboratory of analyzing the micromanometer LV pressures also provides for a calculation of the first derivative of LV pressure (dP/dt) at a variable sampling frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Ten additional patients, ages 44-61 years, who had coronary artery disease and underwent LV catheterization and angiography and selective coronary arteriography within 2 months before coronary bypass surgery were also studied. Coronary surgery was done because of chronic angina in all 10 Thin sections (0.5 ,um) for electron microscopic examination were cut with a microtome (LKB Ultratome III), mounted on uncoated copper grids, stained with saturated aqueous uranyl acetate and lead citrate and evaluated with an electron microscope (Philips EM 300). Sections were put on a grid and localized at low-power magnification under the electron microscope.…”
Section: Methods Patientsmentioning
confidence: 99%
“…For the above reasons, we concluded that ventricular mass could be calculated in patients with single ventricle by basically the same method with the use of a shell model in left ventricle. 16 Confirmation of the method for measurement of the wall thickness from the cineangiogram is possible with other, more direct, methods such as echocardiography and autopsy. We evaluated wall thickness by two-dimensional echocardiography in eight patients with each type of single ventricle and obtained a significant linear correlation between the cineangiographic (y) and echocardiographic (x) measurements: y(mm) -0.984x -0.166 (r = .99, p <.O01).…”
mentioning
confidence: 99%